PEMBUATAN MEDIA PEMBELAJARAN PADA KOMUNITAS KAGEM JOGJA DALAM PENINGKATAN PENANAMAN PENDIDIKAN KARAKTER MELALUI BUDAYA 5S - Yudaninggar, Kartika Sari; Agusta, Rivga; Haryoko, Haryoko; Wijaya, Berlian Aji Putra; Vianda, Viki Okta; Prasetya, Muhammad Rifai Candra; Putri, Belinda; Romadhon, Shahrul Amir (Jurnal Abdi Insani, 2024)
The social environment and social media are some factors that cause children to need help implementing 5S character education. Children and teenagers tend to be more easily influenced by their surroundings, including their peers. Associating with peers who ignore good manners can hinder internalizing these values. The managers and volunteers of the Kagem Jogja Community also experience this. This community is a non-profit learning house for children in the Sardonoharjo area, Ngaglik Sleman, Yogyakarta. This community service takes the form of creating learning media to stimulate the cultivation of character education through 5S culture in the Kagem Jogja community. This activity aims to help Punggawa (volunteers) deliver 5S character education material using learning media. The hope is that it will make delivering 5S character education material easier for children and that children will also more easily understand the material presented. The method for implementing this activity consists of 5 stages: discussion of partner needs, analysis of partner problems, collection of materials and materials, creation of learning media, delivery of learning media to partners, and evaluation stage. The result of this community service activity is the availability of 2 learning media in the form of posters and videos, which can be used to convey material about 5S character education to children in the Kagem Jogja Community. The conclusion from this service in the form of making learning media is that this learning media helps the retainers (volunteers) and will use this learning media to convey 5S character education material to children.